1981
DOI: 10.1029/ja086ia04p02411
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous rocket‐borne beacon and in situ measurements of equatorial spread F—Intermediate wavelength results

Abstract: A high-performance rocket carrying a four-frequency, phase-coherent beacon and full complement of in situ diagnostic instrumentation was launched into active equatorial spread F on July 17, 1979. In this paper we report the results of spectrally analyzing the beacon phase-scintillation and Langmuir probe data. By using simultaneous backscatter data from the Altair radar we were able to establish that the scintillation develops in high-density regions adjacent to the prominent plume structures and associated de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(76 citation statements)
references
References 31 publications
3
71
2
Order By: Relevance
“…These spectral index values, though slightly higher than those reported by Rino et al (1981), can be interpreted in terms of GRT instability. Thus the intermediate irregularities, observed over SHAR, appear to be generated through GRT instability and the dominant contribution to the growth is by gradient drift instability and not by RT instability.…”
Section: Intermediate Scale Irregularitiescontrasting
confidence: 38%
See 2 more Smart Citations
“…These spectral index values, though slightly higher than those reported by Rino et al (1981), can be interpreted in terms of GRT instability. Thus the intermediate irregularities, observed over SHAR, appear to be generated through GRT instability and the dominant contribution to the growth is by gradient drift instability and not by RT instability.…”
Section: Intermediate Scale Irregularitiescontrasting
confidence: 38%
“…Woodman and LaHoz (1976) ®rst identi®ed valley region irregularities below the main plumes in the RTI radar maps obtained from Jicamarca. Vickrey et al (1984) studied electron density irregularities observed in the F region valley, which were obtained from ®xed bias LP¯own on two rockets launched from Natal, Brazil (Kelley et al, 1976(Kelley et al, , 1979Costa and Kelley, 1978) and from Kwajalein Atoll (Szuszczewicz et al, 1980Rino et al, 1981;Kelley et al, 1982b). During these twō ights quasi-sinusoidal¯uctuations in the F region valley (170 to 200 km) were observed where the local zero order vertical plasma density gradient nearly vanishes.…”
Section: Intermediate Scale Irregularitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the same flight Costa & Kelley (1978) found a power law of the type k n with spectral index n = -2.0 for the steep coherent density structures of scale size (scale size λ = 2π/k where k is the wave number) in the range between 10 km and 10 m (k in the range between 0.628 km -1 and 628 km -1 ) in the bottom side F-region. Rino et al (1981) found that for electron density irregularities with scale sizes between 5 km and 500 m (k between 1.257 km -1 and 12.57 km -1 ) the spectral index n ranged between -1.2 and -2.5 and for irregularities with scale sizes between 50 m and 500 m (k between 125.7 km -1 and 12.57 km -1 ) the n value was between -2.3 and -3.4 indicating steeper spectra for altitudes below 370 km. For higher altitudes the observed n values ranged between -1.2 and -2.6.…”
Section: Lp -Upleg Spectramentioning
confidence: 99%
“…Several rocket campaigns have been reported for studying the phenomenon of spread-F in the American region (Kelley et al, 1976;Morse et al, 1977;Rino et al, 1981;Szuszczewicz et al, 1981;Kelley et al, 1982;Hysell et al, 1994) and a few campaigns in the Indian zone Prakash et al, 1991;Sinha et al, 1999;. Kelley et al (1982) reported that at altitudes above about 280 km the electron density spectrum varied as k −5 while the electric field fluctuations showed a power law dependence of k −3 .…”
Section: Introductionmentioning
confidence: 99%